Waste management and international environmental law: emerging trends and implication in Nigeria (2009)
A realization of the necessity for resource sustainability, minimization of waste gene ration, waste conversion, recycling, reuse and proper disposal which will lead to a globally healthy environment, has informed this work. This studies intends to examine some emerging trends, in international environmental law, especially with respect to waste minimization, recycling, recovery, and reuse, and the need for sustainable development in the context of a globalizing world. It will consist of an introduction, an examination of global emphasis on sustainable development, globalization of environmental law, legal international environmental regulation, national domestication of environmental regulations, the nexus between the trends identified, including a global emphasis on sustainable development, and the waste conversion to wealth drive all over the world. The article ends with some recommendations and a conclusion.